Criando o Sentido: a Participação de Textos Literários na Aprendizagem de Leitura em Língua Estrangeira - Souza, Patrícia Nora de (The ESPecialist, 2012)
A comparative study of the performance of two groups of readers - exposed/non-exposed to literary texts - shows a better performance of the “literary” readers, proving the hypothesis that the development of reading skill benefits from the use of a more elaborate linguistic material, whose processing requires the critical intervention of the reader.